Teaching Style as a Reflection of Understanding Christian Ethics - Ezra S. G. Siburian; Jely Riskina Br. Sinaga; Sandy Ariawan (EXOUSIA : Jurnal Pendidikan Agama Kristen, 2022)
Christian ethics is the basis in the teaching style of a teacher, especially the Christian Education teacher, but in practice there are still many teachers who do not fully apply Christian ethics in the basic teaching process. This research aims to find out and evaluate how students' understanding of the character of teachers in teaching styles so that later when students are ready to teach they already know how good Christian ethics are for them to apply in the teaching world. The locus of penelitian is located on a Christian campus in North Sumatra, with student respondents from that campus. From this research, it was revealed that students' understanding of the teacher's Christian ethics and in teaching is quite good but still needs to be improved. The effect of understanding Christian ethics on teaching style was 46.1%. Thus, every teacher in teaching is important to improve and pay attention to Christian ethics in teaching so that the successor of the nation is not misguided and to be equipped with good and correct Christian ethics.